Transcultural turbulences: towards a multi-sited reading of image flows - Brosius, Christiane; Wenzlhuemer, Roland (Springer, 2011)
"Today, hardly anything moves as fast across the globe as images and media. This fact opens new avenues to explore social and cultural change, but also poses new theoretical challenges of how to grasp and better understand these changes and flows. Moreover, such movements across geophysical and cultural borders have a historical depth that enables us to explore globalisation and localisation in new ways. Transculturality is still a relatively new field of research in the Humanities through which we sharpen our competence and 'literacy' to come to terms with the complexity of globalised cultures. This volume ventures into new domains of research on the transculturality of images and addresses the need to develop new or modify established often ethno- and Eurocentric interpretations of what happens when images travel. It does so by bringing together cutting-edge research from fields such as art history, cultural anthropology, colonial history, Islamic studies, religious studies and literary criticism"--Provided by publisher
Literaturangaben
Keywords: Westliche Welt; Asien; Konferenzschrift -- 2009 -- Heidelberg; Kulturübertragung; Visuelle Medien; Massenkultur